Design, synthesis and characterization of hybrid coatings suitable for geopolymeric-based supports for the restoration of cultural heritage. Issue 1 (February 2020) - Ielo, I; Galletta, M; Rando, G; Sfameni, S; Cardiano, P; Sabatino, G; Drommi, D; Rosace, G; Plutino, M R
Abstract: Geopolymers are inorganic materials that form long-range, covalently bonded, networks; they are materials similar to ceramics, whose components are mainly aluminium and silicates. Any inorganic source of silica and alumina, dissolved in the alkaline solution, acts as a precursor of geopolymers. The type of clays most commonly used in the synthesis of geopolymers is based on kaolinite. The present work concerns the modification of the geopolymer at the chemical and nanostructural level, through the design and development of hybrid coating sol-gel formulations to improve characteristics such as mechanical strength, chemical inertness, heat resistance and porosity for possible use in the restoration and conservation of cultural heritage. The methods of functionalization of the geopolymers here shown are: (i) the treatment of the geopolymeric surface, post-drying, through the application of the sol-gel directly on the monolith, for a modification of the surface properties; (ii) the pretreatment of the geopolymeric mixture, through the addition of the alkoxysilane which can induce a homogeneous consolidation of the molecular structure, implementing the properties of the entire monolith. The employed alkoxysilanes differ according to the length of the hydrocarbon chain and the presence of halogen atoms. Hydrophobicity tests were performed on these formulations.